IDENTIFIKASI DIMENSI ENTREPRENEURIAL INTENTIONS PADA WANITA PENGUSAHA (Studi Pada Anggota Ikatan Wanita Pengusaha Indonesia Cabang Kota Bandung) - Wazdi, Adi Indradi (STIBANKS Al Ma'soem Bandung, 2018)
The purpose of this research is to identify the dimensions of Entrepreneurial Intentions on women entrepreneurs in IWAPI Bandung City who are middle aged by using Model Intention Entrepreneurial Event of Shapero (SEE). This research use qualitative descriptive case study (case study). The type of sampling that used in this research is Sampling Network who also called Mechanical Snowball (Snowball Sampling) and there are 4 respondents that researcher pick based on criteria that fit the theme of research. All of them are members of IWAPI Bandung City that truly pioneering efforts from the beginning, either to level SME or entrepreneur with a greater level.The results showed that the triggering factors (trigger event) are dominated by the experience of having negative than positive displacement pull and there is only one respondent who experienced both. According to the SEE theory, perceived desirability dimension does not affect the decision of all respondents in entrepreneurship so that they do not really care the public opinion about the role of women as entrepreneurs because there is not any respondents who own desire from the beginning to be an entrepreneur. The main factors that need to be considered is Perceived Feasibility because it proves that a woman entrepreneur with high confidence is capable to maximize the potential of her resources.